FREQUENCY OF HEARING IMPAIRMENT IN METAL INDUSTRY AND REPERCUSSION ON PROFESSIONAL ENABLING OF DEAF - Husnija Hasanbegović; Esad H. Mahmutović (Human Research in Rehabilitation, 2011)
The survey has been done on sample of 1252 people. The target was to estimate damage of noise on professional rehabilitation of deaf population, which is mostly directed to professions in heavy industry, for professions in metal industry. Sample has been divided to 3 sub samples: 137 hearing people in metal industry; 106 hearing impaired adults with different professions and control group of 1000 hearing people. The results of survey point that work conditions contribute to hearing damage at employers in metal industry by comparison with hearing impairment of usual population. By comparative analysis of registered hearing impairments concerning age, statistically important difference in frequency of hearing impairment of two sub samples (t= 3.27, sing=.05). The relation between hearing impairment and years of working has been identifi ed at employers in heavy industry, (r=.37).